Development of new prefabricated wall constructed using wood-wool cement composite panel - Md Noha, M.S.; Ahmad, Z.; Ibrahim, A.; Walkerd, P. (Elsevier, 2016)
Sustainability in construction industry has brought new materials to be used as a wall element in building construction in Malaysia. Wood-wool cement composite panel (WWCP) is the wood based product which manufactured from renewable resources, less embodied carbon emission, lightweight, easy to process and fabricate and available to the construction industry to replace less eco-friendly materials such as common brick and other masonry element. In Malaysia, there are increasing interest in using WWCP as a wall element in building construction, however the structural performance under imposed load and the installation technique using this material still not well established. Therefore, this study aims to improve the sustainability in building construction with the development of new prefabricated wall constructed using wood-wool cement composite panel. Two types of fabrication techniques are considered in fabricating prefabricated wallettes with dimension of 1200 mm x 1200 mm (± 30 mm). The wallettes type W1 is the current practiced technique, meanwhile wallettes type W2 is the new proposed fabrication technique. Three replicates of each type of wallettes were then tested under axial compression load in order to investigate their structural performance. The results of experimental testing showed that, the wallettes fabricated using the new fabrication technique significantly increased two times in load carrying capacity compared to wallettes with current practiced technique